ANALYSIS OF THE LONG-RUN RELATIONSHIP BETWEEN ECONOMIC GROWTH AND BANK CREDIT AVAILABILITY IN SOUTH AFRICA. - Chakanyuka, Goodman (International Journal of Finance, 2017)
Purpose: The purpose of this study was to Analyze of the Relationship between Business Cycles and Bank Credit Extension: Evidence from South Africa. The study sought establish the direction of causality between economic growth and bank credit growth in South Africa Methodology: The econometric methodology is used to augment results of the survey study. Granger causality test technique is applied to the variables of interest to test for direction of causation between variables. The study uses quarterly data for the period of 1980: Q1 to 2013: Q4. Business cycles are determined and measured by Gross Domestic Product at market prices while bank-granted credit is proxied by credit extension to the private sector. Results: Results revealed that, that there is a stable long-run relationship between macro-economic business cycles and real credit growth in South Africa. The results show that economic growth significantly causes and stimulates bank credit. The Granger causality test provides evidence of unidirectional causal relationship with direction from economic growth to credit extension for South Africa. The study results indicate that the case for demand-following hypothesis is stronger than supply-leading hypothesis in South Africa. Economic growth spurs credit market development in South Africa. Unique contribution to theory, practice and policy: It proposes practical policy prescriptions to address challenges currently facing South Africa. The other major contribution of this study is that it shall open new avenues for further research on finding causality of the relationship between various proxies of economic growth and financial development adopting the VAR framework